Propuesta de creación de una empresa de servicios de Consultoría especializada en mejoramiento continuo, para optimizar los niveles de productividad de las micro, pequeñas y medianas empresas (Mipyme´s) de Quevedo. - González Mendoza, Guido Iván (2021)
This research was carried out in the city of Quevedo with the aim of proposing the creation of a consulting services company specialized in continuous improvement to optimize the productivity levels of the city's MSMEs. Two surveys were carried out with a Focus Group that represents the population of owners of MSMEs in the city of Quevedo, because they represent future clients of the service offered by the consulting services company specialized in continuous improvement. , through which it was possible to identify the main causes of the drop in productivity levels, in addition to determining the level of acceptance of the company which is greater than 50% which represents a considerable level of acceptance, taking into account the ignorance of the subject on the part of the owners of the MIPYME´S. The execution of the project estimates a total of expenses in the first year of management of $ 43,120.13 and $ 47,824.00 of income, generating an annual profit margin of $ 4,703.87, the amount of services that must be executed to recover the investment amount It is 74, that is to say that with 74 services offered, the equilibrium point would be reached. In addition, the project presents an internal rate of return of 37%, which indicates that it is a profitable project, generating a cost-benefit ratio of $ 2.84. Despite the fact that the percentage of gross profits estimated for the first year of execution of the company is not very high, it is predicted that with the passing of the years and the levels of growth that the company can achieve, these may rise, obtaining percentages profit of up to 30%. Keywords: optimization, productivity, MIPYME´s, standardization